BRIDGING WESTERN LEARNING THEORIES AND ISLAMIC EDUCATIONAL PHILOSOPHY: A PHENOMENOLOGICAL INQUIRY INTO KURIKULUM BERBASIS CINTA - Fathurohim; Muhamad Habib; Ahmad Maliki; Imam Tobroni (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
Contemporary educational discourse often faces a dichotomy between rigid behavioral measurement and fluid humanistic development, frequently neglecting the spiritual-emotional essence in Islamic contexts. This study explores the philosophical and practical integration of Behaviorism, Constructivism, and Humanism within the framework of a "Love-Based Curriculum (Kurikulum Berbasis Cinta) from the perspective of Islamic educational philosophy. The primary purpose of this research is to investigate how Islamic education teachers perceive and implement this synthesis to bridge modern Western pedagogical theories with traditional Islamic values. Employing a qualitative approach with Interpretative Phenomenological Analysis (IPA), the study gathered data through in-depth interviews with educators selected for their commitment to compassionate pedagogy. The results indicate that "Love" serves as the foundational bridge, where Behaviorism is reinterpreted as Uswah (exemplary habituation), Constructivism is manifested through Tafakkur (reflective meaning-making), and Humanism is grounded in the honoring of Fitrah (innate potential). The study concludes that a Love-Based Curriculum offers a robust philosophical framework that transcends mere instructional techniques, positioning the teacher as a Murabbi who harmonizes psychological efficiency with spiritual depth. This research suggests that such a synthesis is essential for creating a holistic educational environment that fosters both intellectual competence and moral integrity in the modern era